Penatalaksanaan fisioterapi pada kasus bell's palsy sinistra - ISTIQOMAH, DIYAN NURUL; Dwi Rosella Komalasari, S.Fis, M.Fis (2014)
Background: Bell's Palsy is a symptom of nercvus in the face area that can weakness or paralyzed suddenly on one side of the face. Bell's Palsy in patients with decreased fuctional ability as when drinking or gargling water leak, when eating, food accumulate on one side of the face and people with impaired expression. Purpose: To know the implementation on physiotherapy in improving muscle strength and improve the functional capabilities of the facial muscles in the case of Bell's Palsy using modalities Infra Red ( IR ), Electrical Stimulation ( ES ), facial massage and theraupeutic with mirror exercise. Result : After doing therapy in six times the obtained result an increase in muscle m. frontalis T1 : 0, to T6 : 3, m. orbicularis okuli T1 : 3, to T6 : 3, m. risorius T1 : 0, to T6 : 3, m. buccinator T1 : 0, to T6 : 6, an increase in functional ability in facial muscles break T1 : 0, to T6 : 6, frowned T1 : 0, to T6 : 3, closed eyes T1 : 9, to T6 : 9, smile T1 : 0, to T6 : 9, whistling T1 : 0, to T6 : 3. Conclusion: Infra Red ( IR ), Electrical Stimulation ( ES ), Facial massage and Theraupeutic Exercise with Mirror Exercise can increase muscle strength and functional ability facial muscle strenghtin the case Bell's Palsy sinistra.